Ethical sensitivities, perceptions of integrity, honor pledges, and cheating in higher education - Bennett, Lanice C.; Odom, Summer F.; Wingenbach, Gary; Moody, Whitney (Frontiers in Education, 2025)
IntroductionAcademic misconduct surged during the COVID-19 pandemic as online learning expanded. Understanding factors influencing cheating behaviors is critical for promoting integrity in higher education.MethodsA correlational study was conducted with stratified random samples of undergraduate students (N = 78) at a large U.S. university during Fall 2021. Data were collected via an online survey using validated scales for ethical sensitivity (ESSQ) and integrity perceptions, along with questions on honor code adherence, unauthorized resource use, and demographics. Binary logistic regression identified predictors of cheating in online courses.ResultsStudents reported high ethical sensitivity and strong endorsement of the honor code but low willingness to report violations. Two ESSQ domains—preventing social bias and identifying consequences—were inversely associated with cheating likelihood (p < .05). Belief in the honor code significantly reduced odds of cheating (OR = 0.36, p = .03), while using unauthorized sources for online quizzes increased odds nearly sixfold (OR = 5.92, p = .05). Peer behavior strongly influenced cheating likelihood. No significant relationships were found with gender or class status.DiscussionFindings reveal a gap between students’ stated values and behaviors, highlighting the role of peer norms and unauthorized resources in academic dishonesty. Interventions should emphasize ethical decision-making, peer-led mentoring, and practical applications of honor codes to foster integrity. Implications: Universities should move beyond punitive measures toward restorative approaches that strengthen ethical culture and address emerging challenges such as AI-assisted cheating.